1992
DOI: 10.1190/1.1443195
|View full text |Cite
|
Sign up to set email alerts
|

2-D and 3-D resistivity image reconstruction using crosshole data

Abstract: Theoretical changes in the distribution of electrical potential near subsurface resistivity anomalies have been studied using two resistivity models. The results suggest that the greatest response from such anomalies can be observed with buried electrodes, and that the resistivity model of a volume between boreholes can be accurately reconstructed by using crosshole data. The distributive properties of crosshole electrical potential data obtained by the pole-pole array method have also been examined using the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0
5

Year Published

1996
1996
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(40 citation statements)
references
References 19 publications
(21 reference statements)
0
34
0
5
Order By: Relevance
“…ERT is non destructive, and able to produce 2-or 3D spatial and temporal variation of the soil electrical resistivity, which is tightly linked to variation of soil water content (Zhou et al 2001). ERT has been traditionally used in geological prospecting (Shima 1992;Suzuki and Higashi 2001;Mahmut et al 2006), but is now also often applied in hydrological and environmental studies. Applications include the monitoring of solutes and fluid flow in porous media (Binley et al 1996;Fangary et al 1998;French et al 2002), the monitoring of vadose zone water flow (Daily et al 1992;Backer and Moore 1998;Park 1998;Benderitter and Schott 1999;Binley et al 2002) and soil pollution studies (Ahmed and Sulaiman 2001;Depountis et al 2001).…”
Section: Introductionmentioning
confidence: 99%
“…ERT is non destructive, and able to produce 2-or 3D spatial and temporal variation of the soil electrical resistivity, which is tightly linked to variation of soil water content (Zhou et al 2001). ERT has been traditionally used in geological prospecting (Shima 1992;Suzuki and Higashi 2001;Mahmut et al 2006), but is now also often applied in hydrological and environmental studies. Applications include the monitoring of solutes and fluid flow in porous media (Binley et al 1996;Fangary et al 1998;French et al 2002), the monitoring of vadose zone water flow (Daily et al 1992;Backer and Moore 1998;Park 1998;Benderitter and Schott 1999;Binley et al 2002) and soil pollution studies (Ahmed and Sulaiman 2001;Depountis et al 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, electrical resistivity tomography (ERT) has been reported to be a useful noninvasive prospecting technique. It has been widely used in geolog- ical body prospecting [Shima, 1992[Shima, , 1995Suzuki and Ohnishi, 1995], in evaluating the performance of subsurface structures [Daily and Ramirez, 2000], in mapping solute and fluid movement in porous media [Binley et al, 1996;Ramirez et al, 1993;White, 1994;Yang et al, 1999], and in parameter identification for vadose zone hydrology [Yeh, 1998]. Daily et al [1992] imaged the field resistivity distribution of the vadose zone before and during two infiltration experiments by cross-borehole electrical resistivity tomography.…”
Section: Introductionmentioning
confidence: 99%
“…Since Daniels (1977) and Daniels and Dyck (1984) showed that resistivities measured in borehole(s) can bring detailed information on conductivity variations at large depths and thanks to the development of inversion algorithms (i.e. Oldenburg and Ellis, 1991;Shima, 1992;Loke and Barker, 1996b;LaBrecque et al, 1999), synthetic studies (i.e. Bing and Greenhalgh, 2000;Nimmer et al, 2003), laboratory tests and cross-borehole resistivity experiments were conducted.…”
Section: Introductionmentioning
confidence: 99%